BODY AND SCHOOL PHYSICAL EDUCATION: UNDERSTANDINGS EXPRESSED IN THE NATIONAL CURRICULAR POLICIES - Amaral, Vanessa; Kuhn, Martin; Silva, Sidinei Pithan da [UNESP] (Fundacao Univ Tocantins, 2022)
This bibliographical study shows the understandings of body expressed in curricular policies designed for school Physical Education. It assumes a perspective of body as a cultural construct. The research indicated that the understandings of body expressed in documents over time converge or dialogue with the sociocultural context of the period in which they are produced, now more hygienist/biologicist, now more instrumentalizing and now more culturalist. The body-related critical and reflexive agenda, emergent from the mid-1980s, initiated the movement of valuation of difference, autonomy and diversity in body understanding and expression.
Keywords: Body; School Physical Education; Curriculum Policies